2022
DOI: 10.3390/hydrology9080150
|View full text |Cite
|
Sign up to set email alerts
|

Prediction at Ungauged Catchments through Parameter Optimization and Uncertainty Estimation to Quantify the Regional Water Balance of the Ethiopian Rift Valley Lake Basin

Abstract: Quantifying uncertainties in water resource prediction in data-scarce regions is essential for resource development. We use globally available datasets of precipitation and potential evapotranspiration for the regionalization of model parameters in the data-scarce regions of Ethiopia. A regional model was developed based on 14 gauged catchments. Three possible parameter sets were tested for regionalization: (1) the best calibration parameters, (2) the best validation parameter set derived from behavioral param… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 78 publications
(128 reference statements)
0
3
0
Order By: Relevance
“…The donor catchment is generally selected based on (i) physical features, similarities, and/or (ii) spatial proximity to the targeted ungauged catchment. It has been demonstrated that the geographically closest catchment (or spatial proximity) to the target ungauged catchment is often the best donor catchment [6,43,[49][50][51][52]. The parameter regression method has also been used to transfer parameters to ungauged catchments, with the presumption that the calibrated parameters represent catchment attributes (e.g., slope, elevation, drainage density, land use, soil type).…”
Section: Estimation Of Ungauged Streamflowmentioning
confidence: 99%
“…The donor catchment is generally selected based on (i) physical features, similarities, and/or (ii) spatial proximity to the targeted ungauged catchment. It has been demonstrated that the geographically closest catchment (or spatial proximity) to the target ungauged catchment is often the best donor catchment [6,43,[49][50][51][52]. The parameter regression method has also been used to transfer parameters to ungauged catchments, with the presumption that the calibrated parameters represent catchment attributes (e.g., slope, elevation, drainage density, land use, soil type).…”
Section: Estimation Of Ungauged Streamflowmentioning
confidence: 99%
“…The iteration was run for the simulation period of 1997-2014 and the first 3 years were used for warm-up period. A split sample test was employed to split the remaining years into calibration period (2000)(2001)(2002)(2003)(2004)(2005)(2006)(2007)(2008)(2009) and validation period (2010-2014) on a monthly basis [56].…”
Section: Soil Erosion Modeling Using Swatmentioning
confidence: 99%
“…The donor catchment is generally selected based on: (i) physical features, similarities and or (ii) spatial proximity to the targeted ungauged catchment. It has been demonstrated that the geographically closest catchment (or spatial proximity) to the target ungauged catchment is often the best donor catchment [6,43,[49][50][51][52]. The parameter regression method has also been used to transfer parameters to ungauged catchments, with the presumption that the calibrated parameters represent catchment attributes (e.g., slope, elevation, drainage density, land use, soil type).…”
Section: Estimation Of Ungauged Streamflowmentioning
confidence: 99%